Proteome balancing of the maize seed for higher nutritional value - Wu, Yongrui; Messing, Joachim (Frontiers in Plant Science, 2014)
Most flowering plant seeds are composed of the embryo and endosperm surrounded by maternal tissue, in particular the seed coat. Whereas the embryo represents the dormant progeny, the endosperm is a terminal organ for storage of sugars and amino acids in proteins and carbohydrates, respectively. Produced in maternal leaves during photosynthesis, they are transported to developing seeds during flowering so that during germination they nourish early seedlings growth. Maize endosperm usually contains around 10% protein and 70% starch, and their composition ratio is rather stable, because it is strictly regulated through a pre-set genetic program, which is woven by networks of many interacting or counteracting genes and pathways. Protein, however, is lower in nutritional value mainly due to the high expression of the α-zein gene family encoding lysine-free proteins. Reduced levels of those in the opaque 2 (o2) mutant and α-zein RNAi (RNA interference) transgenic seed is compensated by an increase of non-zein proteins, leading to the rebalancing of the nitrogen sink and therefore producing constant levels of total proteins in the seed. The same rebalancing of zeins and non-zeins has been observed for maize seeds bred for 30% protein. In contrast to the nitrogen sink, storage of sulfur is controlled through the accumulation of specialized sulfur-rich proteins in maize endosperm. However, silencing the synthesis of α-zeins through RNAi fails to raise sulfur-rich proteins. Although overexpression of the methionine-rich δ-zein can increase the methionine level in seeds, it occurs at least in part at the expense of the cysteine-rich β- and γ-zeins, demonstrating a balance between cysteine and methionine in sulfur storage. Therefore, we propose that the throttle for the flow of sulfur is placed before the synthesis of sulfur amino acids when sulfur is taken up and reduced during photosynthesis.